Intracaesarean IUCD: Acceptability, Safety & Efficacy - Vidya A. Thobbi; Nishat Afrin Khan (Al Ameen Medical College, 2018)
Introduction: The present study was done to determine acceptability of intracaesarean PPIUCD and to observe any adverse events and expulsion rates in puerperium. Materials & Methods: A descriptive cohort study was conducted with 400 women undergoing caesarean section. Routine hematological, urine investigation and USG were done. The IUCD was introduced through the lower segment uterine incision during caesarean section and placed at the uterine fund us. The participants were asked to return for follow up at 3rd Post-op day, 2nd& 6th week or earlier in case of any adverse event like pelvic pain, foul smelling vaginal discharge or excessive bleeding. Results: 400 patients were counseled for intracaesarean PPIUCD out of which 100 patients accepted. Majority of the patients (58%) who accepted intracaesarean PPIUCD were in the age group of ≤20-25 years (p>0.05). A significant association was observed between acceptance of IUCD with education, employment and parity. Ease of insertion was observed in 96%of the patients. The most common complications in patients (n-90) after 6 weeks was bleeding (21.1%) followed by strings not visible (15.5%), expulsion (11.1%) and pelvic infection (1.2%). Out of 90 females, 73 (81.1%) patients were fully satisfied after 6 weeks. It was observed none of the patients with Intracaesarean IUCD conceived in 1 year follow up. Conclusion: Intra-operative placement of IUCD is safe and effective method of contraception with low expulsion rate and high continuation rate.